2003
DOI: 10.1023/b:ddas.0000004521.88660.fd
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Intercellular Adhesion Molecule-1 (ICAM-1) During Ischemia–Reperfusion in Human Liver Tissue Allograft: Image Analysis by Confocal Laser Scanning Microscopy

Abstract: We studied and quantified the effect of ischemia-reperfusion on expression of intercellular adhesion molecule-1 (ICAM-1) on sinusoidal endothelial cells and hepatocyte plasma membranes by means of confocal laser scanning microscopy imaging. We found that ischemia induced an increase in ICAM-1 expression on sinusoidal endothelial cells and hepatocytes. After reperfusion, ICAM-1 expression was increased on sinusoidal endothelial cells, whereas it was unmodified on hepatocytes. On the other hand, ICAM-1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, given that these lesions are typically examined by means of FS, they are probably incorporated in other more general studies about digital pathology for intraoperative consultation. Most studies on organ assessment (14/19, 73.7%) were mainly about liver and kidney biopsy,[414151617181920212223242526] while only a small proportion (5/19, 26.3%)[2728293031] dealt with pancreatic islet preparations for transplant. With regard to the type of digital pathology technology used, 12/19 (63.2%) studies discussed DIA applied to LM-acquired images, 4/19 (21.1%) studies used WSI,[15162526] one study involved only static telepathology without DIA,[4] another referred generally to using a “virtual microscope,”[24] and one did not clarify the type of digital pathology used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that these lesions are typically examined by means of FS, they are probably incorporated in other more general studies about digital pathology for intraoperative consultation. Most studies on organ assessment (14/19, 73.7%) were mainly about liver and kidney biopsy,[414151617181920212223242526] while only a small proportion (5/19, 26.3%)[2728293031] dealt with pancreatic islet preparations for transplant. With regard to the type of digital pathology technology used, 12/19 (63.2%) studies discussed DIA applied to LM-acquired images, 4/19 (21.1%) studies used WSI,[15162526] one study involved only static telepathology without DIA,[4] another referred generally to using a “virtual microscope,”[24] and one did not clarify the type of digital pathology used.…”
Section: Methodsmentioning
confidence: 99%
“…examined the expression of different IHC markers in a subset of paired preimplantation and postreperfusion liver biopsies, using DIA of confocal laser scanning microscope images, without comparison to conventional LM IHC. [141920]…”
Section: Methodsmentioning
confidence: 99%
“…(Benkoel et al, 2003) ↑ Acute phase C-reactive protein ↑ (Watchorn et al, 2001) n/e Angiotensinogen ↑ (Li and Brasier, 1996) -? Apoptosis Bcl2 - (Imose et al, 2003) …”
Section: Genesmentioning
confidence: 99%
“…ICAM-1 has been shown to be of particular importance in the adhesion of polymorphonuclear neutrophils (PMNs) to SECs and hepatocytes. After transendothelial migration, PMNs are responsible for the induction and progression of hepatic injury (7,10,12,28). We have shown that ICAM-1 expression is negligible around the central vein (zone III) in the HP group compared with the C group.…”
Section: Discussionmentioning
confidence: 86%